Biological and synthetic template-directed syntheses of mineralized hybrid and inorganic materials. (February 2021) - Wang, Chen-yu; Jiao, Kai; Yan, Jian-fei; Wan, Mei-chen; Wan, Qian-qian; Breschi, Lorenzo; Chen, Ji-hua; Tay, Franklin R.; Niu, Li-na
Abstract: Throughout the course of evolution, organisms have produced biominerals with hierarchical structures derived from organic templates. Over the last couple of decades, scientists have adopted sophisticated structures as templates for preparing pure or hybrid inorganic materials that bear the same morphologies as their biological counterparts. The present review provides a broad overview on the state-of-the-art research in the field of mineralized inorganic and hybrid materials, using functional biological or synthetic templates that have been adopted for biomedical, physical, chemical and environmental applications. The synthesis, properties, and progress of these bio-inspired materials are reviewed to provide a backdrop for future research in various arenas.